Krajnski komedijanti kot del kanonizacijskega procesa preroditeljev v slovenski kulturi - Koron, Alenka (Jezik in slovstvo, 2013)
The article sheds light on some of the significant circumstances of the genesis and performance of Krefts play The Comedians of Carniola as gestures of canonisation with which the author attempted to re-evaluate Linharts role in Slovenian literary history. Nearly forty years later, a play by Mirko Zupančič entitled Thats the Stuff of which the Comedians of Carniola are Made is intertextually connected to Linharts play The Happy Day or Mathias Gets Married and Krefts The Comedians of Carniola, but displays different intentions of the author and the decomposition of the play within the play.
Keywords: Zupančič, Mirko, 1925-; "Iz takšne smo snovi kot kranjski komedjianti"; Slovene literature; slovenska književnost; slovenska dramatika; igra v igri; primerjalne študije; Linhart, Anton Tomaž: Županova Micka; Kreft, Bratko: Krajnski komedijanti; Zupančič, Mirko: Iz takšne smo snovi kot kranjski komedjianti